Dampak Privatisasi BUMN Terhadap Kinerja Keuangan BUMN Indonesia - Annisa, Tapi Omas; Khusnu Alif, Jeffits (E-Jurnal Akuntansi, 2020)
This study aims to examine the differences in state-owned companies before privatization and after privatization is conducted in terms of the company’s financial perfomance. The company’s financial performance uses 10 financial of Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Return On Assets, Return on Investment, Current Ratio, Total Debt to Total Asset Ratio, Total Debt to Equity Ratio, Fix Asset Turnover Ratio, Net Asset Turnover Ratio. This study method uses quantitative research. Data analysis uses mann-whitney different test. The sample of  state-owned companies with a period consisting of 4 years before privatization and 4 years after privatization. Hypothesis test results show that the financial performance of state-owned companies after privatization is better than before privatization. Keywords: Privatization; Financial Performance; State-Owned